1996
DOI: 10.1046/j.1365-2036.1996.108279000.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of nitric oxide synthase activity in the genesis of water immersion stress‐induced gastric lesions in rats: the protective effects of FK506

Abstract: Increase in NO synthase activity might contribute to cytoprotection, and a decrease in activity might be a harmful factor for the gastric mucosa. Preservation of NO synthase activity by FK506 might be involved in FK506's protective effects on the gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 3 publications
(4 reference statements)
0
20
1
Order By: Relevance
“…4,16 Hamaguchi et al 4 reported that the expression of TNF-a in gastric mucosa was increased by water-immersion stress. In addition, antibodies against TNF-a and ICAM-1 significantly attenuated the gastric mucosal injury and neutrophil accumulation caused by Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16 Hamaguchi et al 4 reported that the expression of TNF-a in gastric mucosa was increased by water-immersion stress. In addition, antibodies against TNF-a and ICAM-1 significantly attenuated the gastric mucosal injury and neutrophil accumulation caused by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Recent studies have reported that water-immersion stress-induced gastric mucosal damage could be reduced by the administration of antibody against TNF-a or by the immunosuppressive agent, FK-506. 4,16 Therefore, we have postulated that infiltration of neutrophils in rat gastric mucosa after water-immersion stress could occur in response to the production of proinflammatory cytokines in the gastric mucosa, resulting in the development of gastric mucosal lesions secondary to neutrophil accumulation. Anti-inflammatory effects and several examples of tissue protection exerted by cilostazol have been reported in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ 0.01, **P ϭ 0.001; ***P Ͻ 0.001 compared with control group and myeloperoxidase content. [2][3][4][5] Although various mechanisms are involved in the pathogenesis of water immersion stress-induced gastric lesion, gastric acid secretion is thought to be one of the most important factors. 8,9 In addition, it is well established that various antisecretory agents, such as H 2 -receptor antagonists and proton pump inhibitors, prevent gastric lesions induced by water-immersion stress.…”
Section: Fig 2 Effects Of Cyclosporin a On Ulcer Formation Induced Bymentioning
confidence: 99%
“…1 Recently it has been reported that the immunosuppressive agents cyclosporin A and FK-506 prevented experimental gastric mucosal lesions. [2][3][4][5] Although it has been speculated that the preventive effects were derived from the suppression of cytokine synthesis and neutrophil infiltration, the mechanisms have not been well understood. 2,3 In this study, we investigated the effects of cyclosporin A on gastric ulcer formation induced by Gastric juices were collected by the pylorus ligation method.…”
mentioning
confidence: 98%
“…It has a protective effect (29,73) and is considered to mediate the action of EGF (18), possibly via preservation of GBF/barrier function. It does not influence neutrophilic infiltration or transmucosal fluid flux (29).…”
Section: Other Factors Implicated In Gastric Stress Ulcer Formationmentioning
confidence: 99%